Low Cost Monitoring System of Ground Reaction Force during Normal Gait Cycle for Motion Control and Analysis of Active Ankle Foot Orthosis - Nor Azmi Ab Patar, Mohd; Lee, Hokyoo; Patar, Azim; Azmi Ayub, Muhammad; Hamid, Aminuddin (International Journal of Engineering and Technology, 2018)
Human gaits are complicated motion where it involves synergy of muscle coordination, timing, and balance. Many people are unable to walk with normal gait pattern due to neuromuscular disorder. In order to support the weakness muscle, Active Ankle Foot Orthosis (AAFO) device is developed to provide permanent assistance and control the motion of the foot from being dragged during walking. One of the challenges that researchers has to face with the development of AAFO is providing an efficient transmission and producing continuous and smooth gait cycle. This paper proposes a real time gait phase detection system to control AAFO for rehabilitation and assist ankle motion. Real-time gait phase is obtained by measuring ground reaction force (GRF). The proposed system consists of AAFO equipped with ball screw actuator that provides direct assistance to control ankle joint during dorsiflexion and plantarflexion motion. Three force sensors were embedded insole and an encoder was attached at the ankle joint. The developed control algorithm shows that the real-time GRF measurement has the ability to enhance the AAFO functional performance and improve patientâ€™s gait.Â Â